تأثير أسلوب الصورة والصورة على مهارة كلام طلاب الفصل السابع ‏بمدرسة الهداية المتوسطة ميرو سيكاران لامونجان - Farid Qomaruddin; Khofifah (Institut Kariman Wirayudha Sumenep Madura, 2026)
The aim of this research is to determine the effect of visual and image-based techniques on the speaking skills of seventh-grade students at Al-Hidayah Middle School. The researcher employed a quantitative experimental approach. The sample consisted of 18 students from seventh grade